Exploring Teachers’ Attitudes Toward Teacher Attestation in One Selective School and One Mainstream School in Kazakhstan - Serikbayeva, Zhadyra (Nazarbayev University Graduate School of Education, 2025)
This is a qualitative study that aimed at exploring teachers’ attitudes toward the teacher attestation process in one mainstream school and one selective school in Kazakhstan. Teacher attestation is considered essential for assessing the quality of teaching and promoting professional development. There are, however, concerns about its impact on teachers’ well-being and professional growth. Kazakhstan has introduced a new teacher attestation system quite recently. Before its implementation, the new attestation system was piloted at Nazarbayev Intellectual School (hereinafter, NIS) and adapted to mainstream schools. Therefore, there are attestation differences in the attestation process between NIS and mainstream schools. Therefore, by exploring the teacher attestation system in two types of schools, this study sought to build an understanding about (1) teachers’ attitudes toward the attestation process; (2) its impact on teachers’ well-being, and (3) teachers’ professional development. The data collection instruments included (1) an online questionnaire of 50 teachers to which 35 replied; (2) face-to-face interviews with six teachers: three from a selective school and the other three from a mainstream school; and (3) six reflective notes. The study results indicate that increasing transparency and fairness, balancing accountability and development, maintaining teacher well-being, and integrating professional development into the attestation process can increase its effectiveness and improve teachers’ experiences of it.
Keywords: teacher attestation; professional development; teacher well-being; education reform.; type of access: embargo